2020
DOI: 10.3348/kjr.2019.0824
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diffusion Tensor Imaging Parameters of Hepatic Parenchyma for Differentiation of Biliary Atresia from Alagille Syndrome

Abstract: Objective: To assess diffusion tensor imaging (DTI) parameters of the hepatic parenchyma for the differentiation of biliary atresia (BA) from Alagille syndrome (ALGS). Materials and Methods: This study included 32 infants with BA and 12 infants with ALGS groups who had undergone DTI. Fractional anisotropy (FA) and mean diffusivity (MD) of the liver were calculated twice by two separate readers and hepatic tissue was biopsied. Statistical analyses were performed to determine the mean values of the two groups. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…However, contrary to our ndings, several studies [13,22] have suggested that GGT levels are higher in ALGS patients than in BA patients. We hypothesize that this discrepancy might be related to the younger age of ALGS patients in our study, and the degree of early GGT increase may not be signi cant.…”
Section: Discussioncontrasting
confidence: 99%
“…However, contrary to our ndings, several studies [13,22] have suggested that GGT levels are higher in ALGS patients than in BA patients. We hypothesize that this discrepancy might be related to the younger age of ALGS patients in our study, and the degree of early GGT increase may not be signi cant.…”
Section: Discussioncontrasting
confidence: 99%
“…A study reported by Abdel Razek et al investigated the DTI parameters of the hepatic parenchyma to distinguish BA and Alagille syndrome (ALGS). The DTI parameters such as fractional anisotropy (FA) and mean diffusivity (MD) of the liver showed higher diagnostic performance in BA early diagnosis, which indicates that DTI could be the extra non-invasive imaging tool for BA from ALGS (24). However, the cost of the ultrasound examination is much lower than that of MRI or DTI.…”
Section: Discussionmentioning
confidence: 99%